A Implementation of Online Food delivery App on Multiple Restaurant - Sandiya.B,; R.Greeshma,; P. PAVITHRA,; Kanna, S.Santhosh (International Journal of Psychosocial Rehabilitation, 2020)
The new growth of this web has promoted the enlargement like on-line food services by facultative people to go see, analyse prices and cleverly obtain these potteries. on-line ordering has been rising as a necessity-have a determinant for the dining place market. on-line ordering has become the food industry by passion. Technology sets a buried impact on the market industry, technology has developed the whole structure of the restaurant business, and it will maintain preparing a vast job. A technically improved online food ordering method has become the restaurant’s history drastically and provides a new unusual comfort zone to the people beyond the earth. The principal purpose of this implementation to confuse the kitchen at home and make their delivery service a viable option for an everyday food need with multiple restaurants.